DOI: 10.1016/s0147-9121(07)00007-6
|View full text |Cite
|
Sign up to set email alerts
|

Immigration Amnesty and Immigrant's Earnings

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Gang and Yun (2007) discuss the productivity enhancing effects of a legalization when immigrants are allowed to move from the underground economy to the formal sector. Karlson and Katz (2003) suggest that illegal immigration followed by a probabilistic amnesty can be used as a tool to select high ability immigrants and get rid of less able ones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gang and Yun (2007) discuss the productivity enhancing effects of a legalization when immigrants are allowed to move from the underground economy to the formal sector. Karlson and Katz (2003) suggest that illegal immigration followed by a probabilistic amnesty can be used as a tool to select high ability immigrants and get rid of less able ones.…”
Section: Introductionmentioning
confidence: 99%
“…EW assume that the probability of legalization p i is exogenous and obtain an incentive constraint equivalent to (6). This paper shows that p i can be determined endogenously as a Nash equilibrium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…() who, using a descriptive analysis, concluded that it had no effect on the illegal migration received from Mexico. Gang and Yun () developed a theoretical model to determine the effects that amnesties have on the quantity of migration received by the host country, and also studied the effects of the IRCA on the salaries of immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…The showed that a rich country can use this policy mix to attract cheap foreign workers while avoiding low ability migrants, who, once amnestied, become a burden on the public purse. Finaly, Gang and Yun (2005) reviewed the role immigration amnesties have played in US immigration policy, placing them in the context of similar programs embarked upon by other nations. The theory of amnesties suggests rent seeking, bargaining, and costs as reasons for a country offering an amnesty, often in conjunction with increased border controls, internal enforcement and employer penalties.…”
Section: Introductionmentioning
confidence: 99%